Measuring Poverty in Singapore: Frameworks for Consideration - Donaldson, John A. (Institutional Knowledge at Singapore Management University, 2013)
Singapore does not have an official poverty line. Should there be one? And what are the frameworks that have been used or could be adopted for the measurement of poverty in this country? The Lien Centre for Social Innovation and SMU School of Social Sciences report on their investigation into the complex issue of domestic poverty. Team: John Donaldson, Jacqueline Loh, Sanushka Mudaliar, Mumtaz Md Kadir, Wu Biqi and Yeoh Lam Keong.